Building together : case studies in participatory planning and community building - Katan, Roger; Shiffman, Ron (New Village Press, 2014)
With case studies of neighborhood developments from North and South America, Europe, and Africa that span more than forty years, Building Together offers essential understanding of participatory, collaborative processes that support civil society and sustain democratic cultures. It includes large-scale urban projects such as Listening the City, which engaged more than five thousand New York citizens in the rebuilding effort after the 9/11 attacks on the World Trade Center, and smaller appropriate-technology architectural projects such as self-help assisted housing on Tumaco island at the southern tip of Colombia, South America. Although the cases in this book appear to be highly disparate, involving very different communities and contexts, they were all inspired by the same overarching goal--to help people, whatever their socioeconomic status, better understand the forces acting upon them and organize themselves to have a true say in the construction of their environments. Participatory planning, far from being a fashionable or politically correct form of practice, is probably the only approach that can achieve a community's goal for security, shelter, stability and human happiness. Roger Katan is a French American architect, artist, and educator, renowned as a proponent of the community-based design practices of participatory architecture and advocacy planning. He has been a university instructor, international consultant, lecturer, activist, and author on the subject.Ron Shiffman is the former director of the Pratt Center for Community Development, which he cofounded in 1964. He is currently a professor at Pratt's Graduate Center for Planning and the Environment.